2010 7th International Conference on Service Systems and Service Management 2010
DOI: 10.1109/icsssm.2010.5530086
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance budget planning: A case study for rigid pavement maintenance system in Thailand

Abstract: The expansion of rigid pavement network under the responsibility of the Department of Rural Roads (DORR) has driven DORR to initiate the development of Rigid Pavement Maintenance System (RPMS). The developed system is aimed to analyze concrete or rigid pavement conditions, select the most appropriate treatment technique, and prioritize importance of the maintenance to be performed on different road sections in order to optimize the DORR's limited maintenance budgets. The system consists of two modules: Pavemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Thus, the data are considered not reliable to be used as inputs in order to produce a reliable LCC analysis of rigid pavement maintenance and rehabilitation. This results in the inadequacies of cost data inputs for rigid pavement maintenance and rehabilitation that has been pointed out to be one of the main obstacles to implement LCC analysis in the Malaysian construction industry (Ayob & Abdul Rashid, 2013Ayob, 2014;Suanmali & Ammarapala, 2010). All these data have limited accessibility for public use.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the data are considered not reliable to be used as inputs in order to produce a reliable LCC analysis of rigid pavement maintenance and rehabilitation. This results in the inadequacies of cost data inputs for rigid pavement maintenance and rehabilitation that has been pointed out to be one of the main obstacles to implement LCC analysis in the Malaysian construction industry (Ayob & Abdul Rashid, 2013Ayob, 2014;Suanmali & Ammarapala, 2010). All these data have limited accessibility for public use.…”
Section: Discussionmentioning
confidence: 99%
“…There are several factors that may lead to the deterioration of rigid pavement over time such as increases in traffic volume, movement in underground structure or environmental factor, i.e. moisture and temperature (Public Works Department, 1994;Suanmali & Ammarapala, 2010). The rigid pavement needs to be properly maintained in order to decelerate or reset the deterioration process of the pavement.…”
Section: Rigid Pavement Maintenance and Rehabilitationmentioning
confidence: 99%
See 1 more Smart Citation
“…The maintenance costs of rigid pavement are by far the most challenging to be estimated as there is a need for the establishment of planned and required maintenance works and timings to be done [14]. Besides that, the solid guideline that can assist the transportation agencies in managing the data for maintenance and rehabilitation works have not yet existed as the nature of rigid pavement is complex and complicated [22]. Based on the review of the literature, it was observed that there is no maintenance cost data of rigid pavement available and published in the Malaysian construction industry in order to help the cost estimators to estimate the total maintenance cost of rigid pavement.…”
Section: E Quality Data Input Requirements Of Lcc For Rigid Pavementmentioning
confidence: 99%